When Women Unite…Connecting the Poor : a vision for the Future - B. Renuka Rani (Journal of Agricultural Extension Management, 2025)
Experiments in various developing countries have proved that organizing the poor into small self help groups (SHGs) goes a long way in addressing the problem of poverty. Women are the best change agents to touch the core of poverty. Hence women SHGs pave become the ray of hope for developmental practitioners. Realizing the power and potential of SHGs in alleviating poverty, the Government of Andhra Pradesh has started mobilizing poor women into SHGs. This is a unique phenomenon where the government has taken the role of an NGO and started mobilizing the poor into SHGs